Medical devices for the anesthetist: current perspectives - Ingrande, Jerry (Dove Medical Press, 2014)
Anesthesiologists are unique among most physicians in that they routinely use technology and medical devices to carry out their daily activities. Recently, there have been significant advances in medical technology. These advances have increased the number and utility of medical devices available to the anesthesiologist. There is little doubt that these new tools have improved the practice of anesthesia. Monitoring has become more comprehensive and less invasive, airway management has become easier, and placement of central venous catheters and regional nerve blockade has become faster and safer. This review focuses on key medical devices such as cardiovascular monitors, airway equipment, neuromonitoring tools, ultrasound, and target controlled drug delivery software and hardware. This review demonstrates how advances in these areas have improved the safety and efficacy of anesthesia and facilitate its administration. When applicable, indications and contraindications to the use of these novel devices will be explored as well as the controversies surrounding their use.